The Effectiveness of Extensive Reading in Improving EFL Academic Writing - Linuwih, Endar Rachmawaty (Journal of English Language Teaching and Linguistics, 2021)
This study attempts to answer the question of to what extend extensive reading (ER) could enhance the English of Foreign language (EFL) learners' academic writing. This quasi-experimental study compared two English classes in terms of academic writing improvement after six weeks. This sample of the study was 64 students in a private university in the academic years of 2020-2021. In a traditional English class, the students primarily focused on grammar instruction and writing practice. On the other hand, the students in an ER class engaged in an ER program in and out of class involving the reading-related writing practice. The pretest and posttest were administered to measure students’ writing improvement. The results indicate that students in ER group with more exposure to comprehensible input show statistically significant progress on their posttest, whereas students in a traditional class show a moderate increase.